2002
DOI: 10.1016/s0002-9440(10)64233-2
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Location of Breast Cancer Cells after Spontaneous Metastasis to the Lung

Abstract: In this study, we examined the hypothesis that early pulmonary metastases form within the vasculature. We introduced primary tumors in immunocompromised mice by subcutaneous injection of murine breast carcinoma cells (4T1) expressing green fluorescent protein. Isolated ventilated and perfused lungs from these mice were examined at various times after tumor formation by fluorescent microscopy. The vasculature was visualized by counterstaining with 1,1-dioctadecyl-3,3,3 ,3 -tetramethylindocarbocyanine (DiI)-acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
76
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 15 publications
9
76
1
2
Order By: Relevance
“…Tumor cells from the sLe xpositive variant were observed growing as small clusters in a linear fashion within capillaries. This is in accordance with the results of Wong et al, 45 who demonstrated similar intravascular growth in spontaneous metastasis of the murine 4T1 cell line. Tumor cells from the sLe x -negative variant were observed within capillaries as single cells adjacent to endothelium or as loose clusters of 2-3 cells without strong cell-cell interaction, and linear growth within capillaries was not observed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Tumor cells from the sLe xpositive variant were observed growing as small clusters in a linear fashion within capillaries. This is in accordance with the results of Wong et al, 45 who demonstrated similar intravascular growth in spontaneous metastasis of the murine 4T1 cell line. Tumor cells from the sLe x -negative variant were observed within capillaries as single cells adjacent to endothelium or as loose clusters of 2-3 cells without strong cell-cell interaction, and linear growth within capillaries was not observed.…”
Section: Discussionsupporting
confidence: 93%
“…In these areas, individual tumor cells appeared to be polarized with respect to the Using 4T1 cells as a spontaneous pulmonary metastasis model, it was shown that extravasation was not a prerequisite for metastatic growth. 45 The authors showed that tumor cells proliferated in blood vessels and then proliferating tumor cells massively extravasated via outgrowing the blood vessel. In our model, the differences observed in the morphology of growth patterns in the primary tumor suggest that modification in a carbohydrate epitope and a subsequent alteration in cell-cell adhesion might impact the pattern of micrometastases.…”
Section: Sle X Expression Affected the Morphology Of The Primary Tumomentioning
confidence: 99%
“…4T1 is a mouse transplantable tumor cell line that is highly tumorigenic and invasive. 28 In contrast to previous studies, we have demonstrated that reduced dosage of recSFV provides preferential SFV infection in 4T1 tumor nodules, whereas the dosage increase contributes to broad dissemination of infection in the organism. Moreover, for the first time, the biodistribution of naked SFV recRNA in tumor-free and tumor-bearing mice was investigated on i.v., i.p.…”
Section: Introductioncontrasting
confidence: 99%
“…Several studies showed that an impaired platelet aggregation or a reduced platelet number results in the reduction of metastasis [35]. Our data suggest a direct role of platelets in metastasis in the MT3 model, because the into the surrounding tissue [36]. Additionally, they performed experiments using a spontaneous metastasis model and different cell types [15,31] to confirm these data [36].…”
Section: Discussionsupporting
confidence: 70%
“…It was also shown by the group of Muschel that murine 4T1 breast cancer cells metastasize as single cells to the mouse lungs in a spontaneous metastasis model [36].…”
Section: Discussionmentioning
confidence: 91%